The Magnitude of Hypertension and Its Contributing Factors Among Patients Receiving Antiretroviral Therapy in Public Hospitals in Harar City, Eastern Ethiopia: A Cross-Sectional Study - Dechasa M; Nigussie S; Jambo A; Sime ML; Tamire A; Kitessa M; Degefu N; Dereje J; Demeke H; Legese N (Dove Medical Press, 2023)
Mesay Dechasa,1 Shambel Nigussie,1 Abera Jambo,1 Mekdes Lueleseged Sime,2 Aklilu Tamire,3 Monas Kitessa,4 Natanim Degefu,5 Jerman Dereje,6 Henok Demeke,7 Nanati Legese7 1Department of Clinical Pharmacy, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2Department of Pharmacy, Hiwot Fana Comprehensive Specialized Hospital, Harar, Ethiopia; 3School of Public Health, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 4Department of Pharmacology, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 5Department of Pharmaceutics, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 6School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 7School of Pharmacy, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Mesay Dechasa, Department of Clinical Pharmacy, School of Pharmacy, College of Health and Medical Sciences, Haramaya University, P.O. Box 235, Harar, Ethiopia, Email mesaygc2008@gmail.com; mesay.dechasa@haramaya.edu.etBackground: Although people living with HIV (PLHIV) are surviving longer due to the development of highly active antiretroviral therapy (HAART), hypertension continues to be a significant obstacle for human immunodeficiency virus (HIV) positive patients.Purpose: This study aims to determine the prevalence of hypertension and its contributing factors among patients receiving HAART in public hospitals in Harar City, Eastern Ethiopia.Patients and Methods: A hospital-based cross-sectional study was conducted among adult PLHIV who receive HAART in public hospitals in Harar City, Eastern Ethiopia, from 20 March to 14 April 2023. A simple random sampling technique was employed to select a total of 406 clients (382 participated in the study). Data were collected through patient interview and chart review using a questionnaire. The binary logistic regression was used for data analysis. The association was declared statistically significant at a p-value less than 0.05.Results: The magnitude/prevalence of hypertension was 23% (95% CI: 19.1, 27.5) in study settings from a total of 382 adults who participated in this study. Factors significantly associated with hypertension in a multivariable binary logistic regression model include residence (rural residence, AOR = 1.95, 95% CI: 1.04, 3.65); body mass index (obese, AOR = 4.35, 95% CI: 1.08, 16.77); cigarette smoking (past cigarette smoking, AOR = 4.7, 95% CI: 1.10, 21.8); and HAART regimen change (AOR = 0.44, 95% CI: 0.20, 0.97).Conclusion: The prevalence of hypertension observed among adult PLHIV in the study settings was high. Adults from rural areas, with a history of past smoking cigarette, and obesity need close attention during their clinic visits for more health education to reduce risk factors. The changed HAART regimen was associated with a reduced risk of hypertension. Generally, hypertensive PLHIV need consideration for their double burden of communicable and non-communicable diseases during disease management and hospital guideline development.Keywords: hypertension, associated factors, people living with HIV, Eastern Ethiopia